123I-ioflupane brain SPECT and 123I-MIBG cardiac planar scintigraphy combined use in uncertain parkinsonian disorders. Issue 21 (May 2017) - Nuvoli, Susanna; Spanu, Angela; Piras, Maria Rita; Nieddu, Antonio; Mulas, Aldo; Rocchitta, Gaia; Galleri, Grazia; Serra, Pier Andrea; Madeddu, Giuseppe
Abstract : Abstract: We evaluated the clinical usefulness of the combined use of 123 I-ioflupane brain single photon emission computed tomography (SPECT) and 123 I-metaiodobenzylguanidine (MIBG) cardiac scintigraphy in discriminating uncertain parkinsonism with vascular lesions in striatal nuclei at magnetic resonance imaging (MRI). Forty-three consecutive patients with uncertain parkinsonism and vascular lesions at MRI in striatal nuclei were retrospectively evaluated; the uncertain differential diagnosis was between Parkinson's disease and vascular parkinsonism (PD/VP) in 22 patients, between PD and other neurodegenerative parkinsonism (PD/PS) in 11 patients and between Lewy body dementia and Alzheimer disease (LBD/AD) in the remaining 10 cases. All patients underwent 123 I-ioflupane SPECT with striatal dopaminergic activity determination as binding potentials (BP; cut-off: 3.3). 123 I-MIBG cardiac planar scintigraphy was performed 2 weeks later, in early (15 minutes) and delayed (240 minutes) phases also calculating heart to mediastinum (H/M) ratio (cut-off: 1.56). 123 I-Ioflupane uptake was normal in 9 patients with BP values >3.3, while it was reduced in 34/43 cases with BP values <3.3 at least in one of the striatal nuclei. 123 I-MIBG uptake was normal in 21/43 patients (5 of whom with normal and 16 with 123 I-ioflupane striatal defects) showing the H/M ratio >1.56 in all cases; the uptake was reduced in 22/43 cases, (4 of whom were normal and 18 were with 123 I-ioflupane striatal defects) with the H/M ratio <1.56 in all cases. No statistical differences were found when early and delayed H/M ratios were mutually compared. Combining the 2 radioisotopic procedures, a more reliable diagnosis was achieved in 39/43 cases properly classifying 13 PD, 10 VP, 7 PS, 5 LBD, and 4 AD. However, the diagnosis remained uncertain in four patients with normal 123 I-ioflupane and reduced 123 I-MIBG uptake. The results of the present study confirmed that in uncertain parkinsonian syndromes associated with vascular lesions in striatal nuclei, brain 123 I-ioflupane SPECT alone did not prove able to discriminate between the different forms of disease. Only the association with 123 I-MIBG cardiac scintigraphy, also with the early acquisition alone, allowed the most appropriate diagnosis in 90.7% of our cases. However, patients with normal 123 I-ioflupane and reduced 123 I-I-MIBG uptakes need a close clinical and instrumental follow-up as sympathetic damage could precede striatal disorders in the early stage of PD and LBD.